Α‐galactosylceramide generates lung regulatory T cells through the activated natural killer T cells in mice. Issue 2 (13th November 2018) - Chen, Qianhui; Guo, Xuxue; Deng, Nishan; Liu, Linlin; Chen, Shuo; Wang, Ailing; Li, Ruiyun; Huang, Yi; Ding, Xuhong; Yu, Hongying; Hu, Suping; Nie, Hanxiang
Abstract: Our previous study showed that intraperitoneal injection of α‐galactosylceramide (α‐GalCer) has the ability to activate lung iNKT cells, but α‐GalCer‐activated iNKT cells do not result in airway inflammation in wild‐type (WT) mice. Many studies showed that iNKT cells had the capacity to induce Treg cells, which gave rise to peripheral tolerance. Therefore, we examined the influence of intraperitoneal administration of α‐GalCer on the expansion and suppressive activity of lung Treg cells using iNKT cell‐knockout mice and co‐culture experiments in vitro. We also compared airway inflammation and airway hyperresponsiveness (AHR) after α‐GalCer administration in specific anti‐CD25 mAb‐treated mice. Our data showed that intraperitoneal injection of α‐GalCer could promote the expansion of lung Treg cells in WT mice, but not in iNKT cell‐knockout mice. However, α‐GalCer administration could not boost suppressive activity of Treg cells in WT mice and iNKT cell‐knockout mice. Interestingly, functional inactivation of Treg cells could induce airway inflammation and AHR in WT mice treated with α‐GalCer. Furthermore, α‐GalCer administration could enhance iNKT cells to secrete IL‐2, and neutralization of IL‐2 reduced the expansion of Treg cells in vivo and in vitro. Thus, intraperitoneal administration of α‐GalCer can induce the generation of lung Treg cells in mice through the release of IL‐2 by the activated iNKT cells.